Adsorption isotherms, kinetics and thermodynamic simulation of CO2-CSAC pair for cooling application. (1st October 2018) - Singh, Vinod Kumar; Kumar, E. Anil; Saha, Bidyut Baran
Abstract: This research article proposes to develop a waste heat driven single-stage adsorption-based cooling system by selecting CO2 and indigenous coconut shell based activated carbon (CSAC) as the adsorbate/adsorbent pair. The CO2 adsorption isotherms and kinetics of activated carbon are measured at different temperatures (273–368 K) using volumetric method. In order to illustrate adsorption isotherms, experimental data of CO2 uptake is correlated with the Langmuir and Dubinin-Astakhov (D-A) models. On the other hand, Linear Driving Force (LDF) and Fickian Diffusion (FD) models are utilized to explain adsorption kinetics data. Fugacity and pseudosaturation pressure of CO2 plays a significant role in the estimation of high-pressure CO2 adsorption and thermodynamic properties above the critical temperature of CO2, and these parameters are evaluated using adsorption isotherms data. The key thermodynamic properties and kinetics parameters of the assorted pair are estimated using measured adsorption isotherms and kinetics data which are used for the thermodynamic analysis of CO2 -CSAC pair based cooling system. The maximum theoretical values of SCE and COP of CO2 -CSAC pair are obtained as 12.52 kJ kg −1 and 0.10, respectively at the regeneration temperature of 80 °C along with the evaporator temperature of 15 °C. Highlights: CO2 adsorption isotherms and kinetics onto activated carbon are measured at different temperatures. Two adsorption isotherm and kinetics models are used to correlate the experimental data of CO2 uptake. Thermodynamic simulation of CO2 -CSAC pair based adsorption cooling system is performed. SCE and COP are estimated for single-stage adsorption cooling system at different operating temperatures.